Polemik Dalam Pelaksanaan Pemilu 2024 - Hadji, Kuswan; Saputra, Alan; Firdaus, Elyassin; Hertiana, Essa; Panjaitan, Janter; Surbakti, Syahputra Aditya Kusrin (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Every nation that upholds a democratic system holds general elections (elections) to choose leaders and enact laws. Indonesia is one such nation; elections are held there on a regular basis each year. five (five) years, chosen by popular vote. On voting day for the 2024 Election, voters under the age of 17 who do not yet own an e-KTP are guaranteed to be able to cast a ballot by the Indonesian General Election Commission (KPU). As long as the election is still going on, all they need to bring is a Family Card (KK) in order to vote concurrently. There were several anomalies, anomalies, and a dearth of public understanding on the significance.